2019
DOI: 10.1109/access.2019.2936234
|View full text |Cite
|
Sign up to set email alerts
|

Damping Performance Analysis and Control of Hybrid AC/Multi-Terminal DC Power Grids

Abstract: The voltage-source converter (VSC) based multi-terminal direct-current (MTDC) networks are currently being developed in large-scale power grids for efficient and economical transmission of electrical energy generated from remotely sited renewable energy sources (RESs). As the MTDC network is developed alongside the conventional AC grid, it has transformed the power grid to a hybrid AC/MTDC power network. However, since the MTDC network is controlled via the power electronic converters (PECs), it significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…More specifically, high voltage direct current (HVDC) links are constructed to transmit power generated from remotely sited wind and solar-PV plants to the AC network [12,13]. These structural changes have evolved into hybrid AC/DC power grids, hence stability of the emerging hybrid AC/DC power grids is an important aspect in regards to future power grids [14]. In addition, the distribution grid is also increasingly adopting DC technology due to increased penetration of PEC-interfaced small-scale solar-PV systems and DC loads [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, high voltage direct current (HVDC) links are constructed to transmit power generated from remotely sited wind and solar-PV plants to the AC network [12,13]. These structural changes have evolved into hybrid AC/DC power grids, hence stability of the emerging hybrid AC/DC power grids is an important aspect in regards to future power grids [14]. In addition, the distribution grid is also increasingly adopting DC technology due to increased penetration of PEC-interfaced small-scale solar-PV systems and DC loads [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, stability issues are also originating from the architectural changes in the power grid, such as hybrid AC/DC power grids. Therefore, stability issues emanating from hybrid AC/DC power grids must be thoroughly studied and characterized to minimize the impact on future power grids [14].…”
mentioning
confidence: 99%
“…In [14], the authors extended the damping torque analysis theory to a line-commutated converter based on a voltage source converter (VSC-HVDC) auxiliary damping control to suppress the oscillation of the AC-DC hybrid system. In [15], the authors presented a detailed analytical approach to study the synchronization and damping moments of the AC-DC hybrid power grids. The authors in [16] showed that impedance matching could be used to select the resistance value and the damping controller gained to obtain the maximum damping ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [21] proposes a supplementary control scheme to improve the damping performance of the entire hybrid AC/MTDC power grid. But it only establishes the model of two-terminal AC network and thus cannot be applied to VSC-MTDC.…”
Section: Introductionmentioning
confidence: 99%